Effect of Location, Building Shape, and Wind Turbine Position on the Building for Maximum Wind Energy Potential in Rapid Development Area - Sari, Dany Perwita (LIPI Press, 2014)
High population growth, climate change and energy crises raised awareness in Indonesia especially in Yogyakarta Province which has already arrived at the extreme limit and has been made predominantly for high-rise building design. High-rise building integrated wind turbine is a technology that accelerates wind power from the building elevation. This paper investigated wind velocity on the high-rise building for wind power based on location (wind climate data analysis), building aerodynamic shape and wind turbine position. In the beginning of the study, numerous famous high-rise building was redesigned and simulated using CFD simulation to find the most effective building design. The redesign and simulation were then validated using wind tunnel experiment. Thispaper focuses on guidance resulting on wind power density of Yogyakarta Province to predict the wind energy. The prediction was then combined with best design of aerodynamic building. The result shows that building energy can be optimized through aerodynamic building design, wind turbine position and best geographic area and climate to achieve maximum wind power.